2019
DOI: 10.1002/jcla.22875
|View full text |Cite
|
Sign up to set email alerts
|

The association of five preoperative serum tumor markers and pathological features in patients with breast cancer

Abstract: BackgroundThe utility of frequently used serum tumor markers in breast cancer remains controversial. The study aimed to investigate the role of preoperative carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), cancer antigen 153 (CA153), cancer antigen 724 (CA724), and ferritin (FER) in the management of breast cancer and their relationships with pathological features.MethodsA total of 804 patients with breast mass who underwent breast surgery and 305 healthy volunteers were enrolled. Preoperative serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
5
15
1
Order By: Relevance
“…Lian et al reported that CA153 and CEA did not correlate with ER/PR/Her2 status. However, they stated that CEA levels exhibited statistical differences between PR-negative and PR-positive groups (2). Different from our results, Geng et al concluded that CEA levels in metastatic breast cancer were associated with breast cancer molecular subtypes (48).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Lian et al reported that CA153 and CEA did not correlate with ER/PR/Her2 status. However, they stated that CEA levels exhibited statistical differences between PR-negative and PR-positive groups (2). Different from our results, Geng et al concluded that CEA levels in metastatic breast cancer were associated with breast cancer molecular subtypes (48).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the major advances in BC treatment, the prognosis remains poor. The cancer stage during diagnosis determines BC prognosis ( 2 ). The survival rate of early BC is significantly higher than that of advanced BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinoembryonic antigen (CEA) is a glycoprotein produced by normal cells of the gastrointestinal mucosa which is involved in intercellular adhesion 9 . CEA is one of the first identified tumor markers of human breast cancer which is associated with tumor progression 10 . In veterinary medicine, dogs with mammary gland tumors held higher serum levels of CEA compared to healthy dogs 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of tumor markers had a strong correlation with the advanced stages of cancer [12]. Lian et al in 2019 revealed similar findings, highlighting the role of tumor markers in breast cancer patients [13]. Based on the existing literature, serum CA15-3 can be utilized as a marker for advanced disease and even metastasis [14].…”
Section: Discussionmentioning
confidence: 98%